2019
DOI: 10.1002/mnfr.201900001
|View full text |Cite
|
Sign up to set email alerts
|

As a Histone Deacetylase Inhibitor, γ‐Aminobutyric Acid Upregulates GluR2 Expression: An In Vitro and In Vivo Study

Abstract: Scope γ‐Aminobutyric acid (GABA) possesses extensive physiological functions and can be directly obtained from foods. GABA‐enriched functional foods have been developed and the commercial demands for GABA are increasing. GABA is widely recognized as a central nervous system inhibitory neurotransmitter and plays an important role in some diseases by binding to its receptors. However, some of the functions of GABA are not explained by neurotransmission or GABA receptor pathways. Therefore, this study investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…GABA is an inhibitory neurotransmitter found abundantly in almost all organisms and therefore can be obtained directly from many foods. 247 It is found in over 20 peripheral tissues 248 , and in all regions of the central nervous system. 249 GABA is renowned for its high potency.…”
Section: Amino Acids and Biogenic Aminesmentioning
confidence: 99%
See 1 more Smart Citation
“…GABA is an inhibitory neurotransmitter found abundantly in almost all organisms and therefore can be obtained directly from many foods. 247 It is found in over 20 peripheral tissues 248 , and in all regions of the central nervous system. 249 GABA is renowned for its high potency.…”
Section: Amino Acids and Biogenic Aminesmentioning
confidence: 99%
“… 251 Moreover; GABA was revealed to successfully inhibit class I, II and III histone deacetylases, upregulate H3K9 acetylation and H4K12 acetylation in SH-SY5Y cells; therefore, we cannot rule out epigenetic modulation that may rapidly influence gene expression beyond the BBB. 247 In addition, neurosteroids are highly lipophilic and therefore, readily cross the BBB. 252 Plasma and brain synthesised neurosteroids have demonstrated rapid effects on neuro-excitability via modulation of the GABA-a receptor.…”
Section: Amino Acids and Biogenic Aminesmentioning
confidence: 99%
“…Furthermore, several studies have shown that HDAC inhibitors regulate glutamate receptor expression. ( Bhattacharya et al ., 2017 ; Xing et al ., 2019 ), however, the molecular mechanisms are poorly understood. We found for the first time MeBib, a HDAC6 inhibitor, suppressed the MA seeking response.…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells were inoculated in six-well cell culture plates and cultured into a sub-confluent state. According to our previous study, 21 the cells were pretreated with GABA at a final concentration of 10 nM for 3 h, and then exposed to a final concentration of 10 μM of Aβ. The culture medium was removed after continuous incubation for 24 h, and the cells were washed with phosphate-buffered saline and collected for qRT-PCR and western blotting assays.…”
Section: Methodsmentioning
confidence: 99%